Analysis of the impact of heavy water pollution on algal diversity using spectroscopy and electron microscopy techniques / Review Article - Maarb Salih Al-Maoula; Rand Haider Ali; Noor redha Gummaa; Estabraq Mohammed Ati; Reyam Naji Ajmi (Peerian Journals Publishing, 2025)
Algae play a vital role in maintaining the ecological balance of aquatic systems. They are the primary source in the food chain and contribute significantly to oxygen production through photosynthesis and the reduction of atmospheric carbon dioxide. Recent studies indicate that microalgae are responsible for more than 50% of global oxygen production. Algae also constitute an important nutritional basis for zooplankton and small fish, enhancing the stability of aquatic food chains. However, unregulated industrial expansion has led to the discharge of large quantities of wastewater laden with toxic heavy metals such as lead, mercury, cadmium, zinc, and chromium, causing significant imbalances in algal communities at the physiological, structural, and functional levels
Keywords: Microalgae; heavy metals; industrial pollution; biological indicators